2022
DOI: 10.3389/fneur.2022.964627
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent theta-burst stimulation with physical exercise improves poststroke motor function: A systemic review and meta-analysis

Abstract: BackgroundIntermittent theta-burst stimulation (iTBS) is an optimized rTMS modality that could modulate the excitability of neural structures. Several studies have been conducted to investigate the efficacy of iTBS in improving the motor function of stroke patients. However, the specific role of iTBS in motor function recovery after stroke is unclear. Hence, in our study, we performed a meta-analysis to investigate the efficacy of iTBS for the motor function improvement of stroke patients.MethodsMEDLINE, Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Besides, standard 600-pulse stimulation showed a better effect on motor function improvement compared to 1200 pulses. The results are consistent with previous studies [ 16 , 52 , 53 ]. Additionally, two studies [ 34 ] integrated different forms of rTMS and reported that bi-hemispheric stimulation (1 Hz rTMS to the UH M1 and iTBS to the AH M1) was associated with better motor performance when compared to unilateral modulation [ 54 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Besides, standard 600-pulse stimulation showed a better effect on motor function improvement compared to 1200 pulses. The results are consistent with previous studies [ 16 , 52 , 53 ]. Additionally, two studies [ 34 ] integrated different forms of rTMS and reported that bi-hemispheric stimulation (1 Hz rTMS to the UH M1 and iTBS to the AH M1) was associated with better motor performance when compared to unilateral modulation [ 54 ].…”
Section: Discussionsupporting
confidence: 94%
“…Although studies on TBS intervention for specific post-stroke dysfunctions have been published [ 15 , 16 ], there is still a lack of conclusive statements on the role of TBS in stroke rehabilitation. This review aims to summarize the current evidence of TBS in the rehabilitation of various post-stroke dysfunctions, providing directions for clinical application and future research using TBS to promote stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…These scores reflect on coordinated and dissociative movements. However, they concluded that the positive effect of iTBS on motor function was only evident in chronic stroke patients, not in those in the subacute phase (Gao et al, 2022). These findings highlight TMS, particularly when paired with physical exercise, as a promising intervention for stroke rehabilitation.…”
Section: Strokementioning
confidence: 99%
“…Parkinson's disease High frequency, bilateral, multi-session rTMS over M1 (Yang et al, 2018) Priming with TMS prior to large-amplitude training (Fox et al, 2012;Osborne et al, 2022) Needs more research Stroke iTBS for individuals with chronic stroke (Gao et al, 2022) Concurrent iTBS with UE CIMT therapy (Nesin et al, 2019) Needs more research TBI rTMS for management of mild TBI symptoms (Buhagiar et al, 2020) Priming with TMS prior to vestibular therapy (Schlemmer and Nicholson, 2022) Needs more research…”
Section: Clinical Readinessmentioning
confidence: 99%
“…In the iTBS, a 2 s train of TBS is repeated every 10 s for a total of 190 s (600 pulses) ( Huang et al, 2005 ). Currently, the main target of stimulation is the primary motor cortex (M1) over the ipsilateral hemisphere when iTBS is used to treat poststroke upper limb motor dysfunction ( Gao et al, 2022 ; Huang et al, 2022 ; Tang et al, 2022 ). Although iTBS appears to be a promising treatment for upper limb motor recovery in stroke patients, it is noteworthy that the evidence for beneficial effects of iTBS on post-stroke upper limb motor dysfunction is inconclusive.…”
Section: Introductionmentioning
confidence: 99%